Formulasi Constitutional Ethics sebagai Instrumen Pengawasan Imparsialitas Eksekutif dalam Tahapan Pemilu - Muhamad Irwan; Rizky Perdana Bayu Putra (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examines the urgency of formulating constitutional ethics as a legal instrument to oversee the impartiality of the executive branch during the electoral process in Indonesia. Executive dominance has the potential to lead to abuse of power, the politicization of the bureaucracy, and the use of state resources for electoral purposes, while election regulations still focus on administrative and criminal violations. This study employs a normative legal methodology using legislative, conceptual, and comparative approaches. The findings indicate that constitutional ethics plays a strategic role as a bridge between legality and morality in state governance. The formalization of constitutional ethics is necessary to establish standards of conduct for public officials, strengthen ethical accountability, and safeguard executive neutrality and democratic integrity in the conduct of elections.